Organizational behavior - Robbins, Stephen P. 1943-; Judge, Tim (Pearson, 2011)
For undergraduate and graduate courses in organizational behaviour. This edition contains new material on responding to global and cultural diversity with discussions of globalization, workforce diversity and ethics. There is an additional chapter on leadership and expanded coverage of interpersonal and behavioural skills.